Measurement Analysis of the Level of E-Commerce Adoption Readiness in SMEs Using Technology Readiness Index Method - Sulistyowati; Haniwijaya Pahlawansah; Chevy Herli Sumerli A; Cut Susan Octiva; Humaidah Muafiqie (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to determine the extent of readiness for adoption and what factors influence readiness for e-commerce adoption. This study uses the Technology Readiness Index (TRI) model and the Information Technology Adoption Model by adding the variables of customer readiness, competitive pressure, and IT adoption. The population in this study is SMEs. The sample used from this population is 150 respondents with the purposive sampling technique. This study used quantitative methods with analysis techniques using PLS-SEM and data analysis using SmartPLS version 3.0. The results of this study indicate that six out of ten hypotheses are accepted. So that the factors that influence the readiness of e-commerce adoption are the optimism variable for the customer readiness variable, the optimism variable for the competitive pressure variable, innovativeness for the customer readiness variable, innovativeness for competitive pressure, discomfort for customer readiness, and competitive pressure for IT adoption.